EFEK EKSTRAK ETANOL 70% HERBA KEMANGI (Ocimum americanum L.) SEBAGAI PENURUN KADAR ASAM URAT PADA TIKUS JANTAN Galur Sprague Dawley - Yesi Restina; E. Mulyati Effendi; Ike Yulia W. (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2018)
This study aims to determine the influence of ethanol extract 70% herbal basil in the uric acid levels in Sprague, Dawley strain. The test animals used were 25 mice that were divided into 5 groups, each consisting of 5 mice. Group Treatment I Allupurinol 5.04 g/200 g BB as control (+), treatment II CMC 0.5%/200 g BB as Control (-), treatment III ethanol extract 70% herbal basil 0, 4g/200g BB (dose 1), treatment IV ethanol extract 70% herbs basil 0, 8g/200g BB (dose 2) and V treatment ethanol extract 70% herbals Basil 1, 6g/200g BB (dose 3). The results showed that the administration of basil extract of herbals can reduce levels of uric acid during treatment 15 days, the most effective dose is dose 2 (0, 8g/200g BB).